(3MGTjI GdOhGfj Ydi TQM GdTQhGfjs - (3GdOhGfj GdUOjbj, LdGd GdOjf, eMeO Hf CSYO, J (B918 (3g`s ((3fGMjI TQhGfs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3bGd GdTGQM (B: (3ef Ydjg , gPG ETGQI Edi eYfi GdefI hHjGf GSJYeGdgG dG HjGf GdGTJbGb aEf GdeUOQ djS HeTJb Yf GdaUd Ydi ePgH GdHUQjjf haj daX YdjfG hYdjg GjeGA Edi gPG bGd (B...s
(3BNQgG (B:s
... (3jfajg YOe GdGSJYLGd ceG YQaJ eeG PcQg Ydi GdELeGd , bhdg Ch hVY ZjQ ZjQ GdSHH ecGf GdSHH gPG (B... (3aj GdHOjgj JCed bhdg dG jMJGL Edi GdGSJOdGd Ydjg (B... (3JeJs
(3JHUQI GdYfhGf (B:s
(3TQM GdTQhGfj Ydi BOGH eMeO Hf CTQa GdSeQbfOjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\32s
(3cTa GdXfhf (B1\39s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs